2011
DOI: 10.5785/23-2-52
|View full text |Cite
|
Sign up to set email alerts
|

Investigating students’ beliefs about language learning

Abstract: There is widespread current interest in language learning studies regarding the extent to which student beliefs can influence the language learning process. Whilst institutions may set up frameworks to enable students to learn languages successfully, many researchers contend that ultimately it is the belief systems of the students themselves which will contribute most to the final outcome of the teaching process. This article explores the idea that the language learning process among students is substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 14 publications
2
11
0
3
Order By: Relevance
“…In this regard, teacher and parents as the influential people in English learning process will play the important roles in establishing the valuable, creative, and interesting English learning experiences that will drive the students to hold or keep on the positive beliefs in order to improve their English achievement. It was in accordance with Horwitz in Boakye (2007) who proves that the beliefs the students have affect how they go about doing it.…”
Section: Students' Beliefs About English Language Learningsupporting
confidence: 85%
See 2 more Smart Citations
“…In this regard, teacher and parents as the influential people in English learning process will play the important roles in establishing the valuable, creative, and interesting English learning experiences that will drive the students to hold or keep on the positive beliefs in order to improve their English achievement. It was in accordance with Horwitz in Boakye (2007) who proves that the beliefs the students have affect how they go about doing it.…”
Section: Students' Beliefs About English Language Learningsupporting
confidence: 85%
“…This result was inconsistent with Angelianawati (2012) and Hayati (2014) who found that beliefs about language learning in general had significant correlation with English academic achievement. Horwitz in Boakye (2007) says that the beliefs students have about language learning can affect how the students go about learning it. Boakye (2007) emphasizes that learners' beliefs have an important role in students' experience and their success or failure as language learners also supports their beliefs.…”
Section: The Correlation Of Beliefs About English Language Learning mentioning
confidence: 99%
See 1 more Smart Citation
“…the teaching and learning of English using WhatsApp. In addition, regards of the nature of belief per se, this study refer to Borg's (2001) definition of belief. Borg (2001) posits that beliefs are germane with the proposition or judgment hold true by individuals and therefore inflame commitment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, regards of the nature of belief per se, this study refer to Borg's (2001) definition of belief. Borg (2001) posits that beliefs are germane with the proposition or judgment hold true by individuals and therefore inflame commitment. Hence, the beliefs of the teachers of this study relate to verbal statements of proposition or judgment perceived true by the teachers.…”
Section: Introductionmentioning
confidence: 99%